The rapid detection of E. coli 0157 Antigen in meat products by using ELISA Test Kit - Abdulrasool, Maithem Ihsan (The Iraqi Journal of Veterinary Medicine, 2011)
This study was conducted for rapid detection of contamination of meat products with E. coli 0157 by usage of ELISA test kit as one of the most rapid and newest test. The study showed the efficiency of ELISA test kit used in this study in detection of bacteria antigen in meat products samples of raw beef meat , kabab and beef burger which subjected to improper storage conditions or undercooked and hence when some peoples uptake some of these products they suffered from clinical intoxication signs like diarrhea ,vomiting and hyperthermia. The kit showed the presence of (9) samples positive among (90) samples ; (2) positive out of (30) kabab samples,(3) positive out of (30) beef burger and (4) positive out of (30) raw beef meat after 16 hrs of enrichment of all samples in EC Modified broth including Novobiocin supplement as inhibitor of other bacteria and then the liquid supernatants from all prepared samples got tested by ELISA kit used in this study and the data recovered in less than 1 hr.The study indicated the ability of using ELISA kit for detection of E. coli 0157 antigens in food stuffs and reduce the time for releasing the results in less than 24 hrs when compared with conventional culturing procedure which reuiqred more than 3 days and launch the food products for consumption with focusing on the main point here which is the protection of our consumer safety.